Analisis Yuridis Terhadap Pelaksanaan Pinjam Pakai Barang Bukti Perkara Tindak Pidana - Yeni Suswita; Hery Fadlullah; Nurjannah Nurjannah; Pasten Hard; Marsudi Utoyo (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
The court conducts an examination process known as proof. For the purposes of proof, the presence of objects involved in a crime is also very necessary. These objects are often known as